Factors affecting asphalt concrete permanent deformation: Experimental dataset for uniaxial repeated load test - Albayati, Amjad H. (Data in brief, 2024)
Permanent deformation in asphalt concrete pavements is pervasive distress [1], influenced by various factors such as environmental conditions, traffic loading, and mixture properties. A meticulous investigation into these factors has been conducted, yielding a robust dataset from uniaxial repeated load tests on 108 asphalt concrete samples. Each sample underwent systematic evaluation under varied test temperatures, loading conditions, and mixture properties, ensuring the data's comprehensiveness and reliability. The materials used, sourced locally, were selected to enhance the studyʼs relevance to pavement constructions in hot climate areas, considering different asphalt cement grades and contents to understand material variability effects on deformation. The detailed dataset created from the experimental program acts as a pivotal resource for refining predictive models and optimizing asphalt concrete mixtures and pavement design strategies, aimed at improving pavement performance and longevity under diverse operational and environmental conditions.